2014
DOI: 10.1038/icb.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

The deficiency of Gαq leads to enhanced T‐cell survival

Abstract: We have previously reported that Gαq, the α subunit of the Gq protein, had important roles in dendritic cell migration, B-cell survival and autoimmunity. In this study, we showed that the deficiency of Gαq led to enhanced T-cell survival. Cultured Gnaq(-/-) T cells exhibited survival advantages both in medium alone and in the presence of anti-CD3 stimulation. Gnaq(-/-) T cells still exhibited a survival advantage when they were cultured in the presence of interleukin (IL)-2 or IL-7. Gnaq(-/-) T cells were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
7
12
0
Order By: Relevance
“…Accordingly, in a previous study we showed that upon T-cell receptor ligation, Akt activity was increased in Gnaq-/- T cells in comparison with wild-type T cells, and the survival advantage of Gnaq-/- T cells was significantly attenuated by Akt inhibition. We also proved that Gαq deficiency promotes T cell survival via upregulation of Bcl-xL and downregulation of Fas and FasL expression [14]. Here, we further show that Gαq expression was inversely correlated anti-apoptotic Bcl-2, and directly correlated with pro-apoptotic Bax mRNAs levels in T cells from SLE patients.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Accordingly, in a previous study we showed that upon T-cell receptor ligation, Akt activity was increased in Gnaq-/- T cells in comparison with wild-type T cells, and the survival advantage of Gnaq-/- T cells was significantly attenuated by Akt inhibition. We also proved that Gαq deficiency promotes T cell survival via upregulation of Bcl-xL and downregulation of Fas and FasL expression [14]. Here, we further show that Gαq expression was inversely correlated anti-apoptotic Bcl-2, and directly correlated with pro-apoptotic Bax mRNAs levels in T cells from SLE patients.…”
Section: Discussionsupporting
confidence: 70%
“…We also reported that the protein and mRNA levels of Gαq in peripheral blood lymphocytes from rheumatoid arthritis (RA) patients were significantly lower compared with healthy controls, and that decreased Gαq expression was closely correlated with disease activity [13]. Furthermore, Gnaq-/- T cells showed significant survival advantages both in vitro and in vivo [14]. These studies supported a pivotal role of the Gαq subunit in the pathogenesis of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 90%
“…Gαq-KO mice were derived from the C57BL/6 strain, and genotype identification was based on PCR. 16 All mice were maintained at the Tongji University animal care facility in pathogen-free conditions. The experiments were carried out in accordance with the Tongji University Animal Care Committee guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Gαq has been reported to be involved in the pathways that regulate the migration and survival of T cells. 16,19 We further investigated whether Gαq directly influenced the polarization of T cells. Th1, Th17, and Treg cells, three subsets of CD4 + T cells, were induced from CD4 + T cells using different combinations of cytokines and antibodies as previously described.…”
Section: Gαq Deficiency Inhibits In Vitro Th17 Differentiationmentioning
confidence: 99%
“…With relevance to disease, blocking Gαq ameliorates murine lupus, 8 with overexpression of Gαq linked to pancreatitis, 9 indicating a role for Gαq signaling in disease pathogenesis. In support of this, Gαq is a well-characterized player in the mechanisms driving MS, including the regulation of T-cell survival 10 and migration, 11 and a body of data indicates that targeting Gαq-coupled signaling may by a therapeutic avenue in MS. 12,13 In the present issue of Cellular and Molecular Immunology, Lai et al 14 targeted this link between Gαq signaling and MS using Gαq knockout animals in the EAE model. The results of these experiments were clear-cut.…”
mentioning
confidence: 99%